Collective memories and social roles: the case of the Paris terrorist attacks of 13 November 2015 - Orianne, Jean-François; Heiden, Serge; Klein-Peschanski, Carine; Eustache, Francis; Peschanski, Denis (Frontiers in Sociology, 2024)
This article deals with collective memories of the terrorist attacks that took place in Paris on 13 November 2015. Analysis of a corpus of 934 individual interviews conducted in 2016 revealed the important influence of social roles on the construction of memories and narratives of this event.Application of textometry tools highlighted lexical fields specific to the different social roles played by the interviewees in this social drama, and showed that it was through these specific vocabularies that they remembered and recounted this extraordinary story. Social roles therefore influence the formation of memories both individual and collective, by modulating the way in which individuals select what to remember and what to forget.